Poucher's Perfumes, Cosmetics and Soaps (10th Edition) - Butler, Hilda (Kluwer Academic Publishers, 2011)
A very comprehensive book about perfume, soap and cosmetic industry. Decribes in great detail about the industry historically. This book also provides information about where the flow, tendency and future of the perfume is going.